Heat Capacity and Thermodynamic Properties of Cesium Pentaborate Tetrahydrate - Kangrui Sun; Panpan Li; Long Li; Yafei Guo; Tianlong Deng (Journal of Chemistry)
This paper reports the molar heat capacities of β-CsB5O8·4H2O, which were measured by an accurate adiabatic calorimeter from 298 to 373 K with a heating rate of 0.1 K/min under nitrogen atmosphere. Neither phase transition nor thermal anomalies were observed. The molar heat capacity against temperature was fitted to a polynomial equation of Cp,m (J·mol−1·K−1) = 618.07702 + 39.52669[T − (Tmax + Tmin)/2]/(Tmax − Tmin)/2] − 3.46888[(T − (Tmax + Tmin)/2)/(Tmax − Tmin)/2]2 + 7.9441[(T − (Tmax+ Tmin)/2)/(Tmax − Tmin)/2]3. The relevant thermodynamic functions of enthalpy (HT − H298.15), entropy (ST − S298.15), and Gibbs free energy (GT − G298.15) of cesium pentaborate tetrahydrate from 298 to 375 K of 5 K intervals are also obtained on the basis of relational expression equations between thermodynamic functions and the molar heat capacity.